2020
DOI: 10.1038/s41598-020-76361-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying environmental risk factors for inflammatory bowel diseases: a Mendelian randomization study

Abstract: Several studies have examined environmental factors and inflammatory bowel diseases (IBD) using traditional approaches; however, provided results are still conflicting. Our aim was to determine whether lifestyle and nutrient exposures, related to IBD in observational meta-analyses, influence IBD risk using a Mendelian randomization (MR) approach. A two-sample MR approach was applied on summary-level genome-wide association results. Genetic variants strongly associated with measures of tobacco smoking, obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
1
37
2
Order By: Relevance
“… 38 Furthermore, a recent MR study revealed a positive association between genetically predicted high serum vitamin B12 concentrations and risk of inflammatory bowel disease, especially Crohn’s disease. 39 This may be of relevance as patients diagnosed with inflammatory bowel disease have an increased risk of developing colorectal cancer. 40 …”
Section: Discussionmentioning
confidence: 99%
“… 38 Furthermore, a recent MR study revealed a positive association between genetically predicted high serum vitamin B12 concentrations and risk of inflammatory bowel disease, especially Crohn’s disease. 39 This may be of relevance as patients diagnosed with inflammatory bowel disease have an increased risk of developing colorectal cancer. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the rapid development of genome-wide association study (GWAS) and accumulation of publicly available GWAS summary statistics, MR design based on two-sample setting is becoming more flexible and accessible. Several MR studies have identified causal risk factors of IBD, such as body fat percentage ( Carreras-Torres et al, 2020 ) and ankylosing spondylitis ( Cui et al, 2020 ). Also, a MR study clarified the causal relationship between NAFLD, type 2 diabetes (T2D) and obesity ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have found interactions and pathological similarities between IBD and metabolic disorders, including metabolic tissue disorders, inadequate immune response, and inflammatory response [ 53 ]. Patients with non-alcoholic fatty liver diseases (NAFLD) or a high body fat percentage are at higher risk for IBD [ 54 , 55 ]. Combined with the patient’s clinical symptoms, MRI fat quantification could be applied to CAD of IBD and diabetes in future.…”
Section: Application Of DL In Digestive System Imagingmentioning
confidence: 99%